One and a half syndrome following penetrating head injury: Case report. (July 2017) - Voisin, Mathew R.; Sasikumar, Sanskriti; Russell, Jeremy H.; Zadeh, Gelareh
Highlights: One and a half syndrome is a rare disorder of eye movement. This is the first case report to describe a traumatic cause of the syndrome. This case illustrates the importance of clinico-radiological interaction. Abstract: The authors report a case of a 22-year-old otherwise healthy female who presented following a head injury during a bar altercation, with no associated loss of consciousness and an unknown mechanism of injury. Examination revealed an isolated 1 cm laceration on the right upper eyelid, superior to her medial canthus. She experienced diplopia on right horizontal gaze due to a left internuclear ophthalmoplegia (INO) with an associated left conjugate horizontal gaze palsy, collectively described as a left one-and-a-half syndrome. CT and MRI demonstrated evidence of a deep penetrating injury above the right medial canthus, traversing the ethmoid and sphenoid sinuses, the dorsum sella, narrowly missing the basilar artery, penetrating the pons, and extending to the floor of the contralateral fourth ventricle. The patient was diagnosed with multiple sinus fractures, lesions in her left paramedian pontine reticular formation (PPRF) and medial longitudinal fasciculus (MLF), and progressive pneumocephalus. She underwent a transsphenoidal endoscopic repair via a vascularized mucosal flap without complication. Postoperatively, the patient's pneumocephalus resolved and her conjugate gaze markedly improved; however, minimal diplopia remained. This case demonstrates the importance of the clinical exam, and its benefit in localizing imaging findings and guiding treatment.